2007
DOI: 10.1590/s0102-76382007000300004
|View full text |Cite
|
Sign up to set email alerts
|

Revascularização do miocárdio com emprego de ambas artérias mamárias internas em pacientes com diabetes mellitus

Abstract: Revascularização do miocárdio com emprego de ambas artérias mamárias internas em pacientes com diabetes mellitusCoronary artery bypass grafting using both internal mammary arteries in patients with diabetes mellitus Abstract Objective: We sought to describe the use of both internal thoracic arteries (ITA) in patients with diabetes mellitus (DM) submitted to a coronary artery bypass grafting (CABG).Method: Between January 1995 to August 2005, 4,569 patients received isolated CABG in our institution. Of the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…In a recent article, Martins et al [22] presented their results of a group of patients submitted to CABG utilizing both ITAs. Of a total of 700 patients enrolled, 552 were non-diabetic and 148 were diabetic.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent article, Martins et al [22] presented their results of a group of patients submitted to CABG utilizing both ITAs. Of a total of 700 patients enrolled, 552 were non-diabetic and 148 were diabetic.…”
Section: Discussionmentioning
confidence: 99%
“…Another study identified PU with 62% in stage I, 29% in stage II and 4% in stage III (8) . Another study found that 45% of PU were in stage I (18) .…”
Section: Rev Esc Enfermmentioning
confidence: 98%
“…Many patients were hospitalized the day before the surgery because they already had preoperative exams while others required several days for taking exams and preoperative preparation. In a study addressing skin care provided to patients who underwent cardiac surgery, the author indicates a high duration of hospitalization as an important factor in the development of skin lesions (8) .…”
Section: Rev Esc Enfermmentioning
confidence: 99%
“…Therefore, alternative arterial grafts have been continuously researched. The most commonly used arterial grafts are the left and right internal thoracic [1,2,[5][6][7][8] and radial arteries [9,10]. The inferior epigastric and gastroepiploic arteries are less frequently used [1,5,7,10].…”
Section: Introductionmentioning
confidence: 99%